Drained lake basins in the area of the 2007 Anaktuvuk River Tundra Fire, North Slope, Alaska - Helena Bergstedt; Benjamin Jones; Guido Grosse; Christopher Arp; Eric Miller; Lin Liu; Daniel Hayes; Christopher Larsen (Arctic Data Center, 2021)
This data set covers the Anaktuvuk River fire site and maps drained lake basins in this area as described by Jones et al (2015). The data set is derived from airborne Light Detection and Ranging (LiDAR) data acquired in 2009 and 2014. The classification of drained lake basins is based on digital terrain models (DTMs) created from the classified LiDAR data and using the a topographic position index (TPI). The TPI output was manually categorized relative to existing surficial geology maps and refined into the following terrain units: (1) drained lake basins, (2) yedoma uplands, (3) rocky uplands, (4) glaciated upland, (5) river floodplain and (6) tundra stream gulches. The drained lake basin class is the subject of this data set publication. Jones, B., Grosse, G., Arp, C. et al. Recent Arctic tundra fire initiates widespread thermokarst development. Sci Rep 5, 15865 (2015). https://doi.org/10.1038/srep15865